Wide distribution of virulence genes among Enterococcus faecium and Enterococcus faecalis clinical isolates - Soheili, Sara; Ghafourian, Sobhan; Sekawi, Zamberi; Neela, Vasantha Kumari; Sadeghifard, Nourkhoda; Ramli, Ramliza; Hamat, Rukman Awang (Hindawi Publishing Corporation, 2014)
Enterococcus, a Gram-positive facultative anaerobic cocci belonging to the lactic acid bacteria of the phylum Firmicutes, is known to be able to resist a wide range of hostile conditions such as different pH levels, high concentration of NaCl (6.5%), and the extended temperatures between 5°C and 65°C. Despite being the third most common nosocomial pathogen, our understanding on its virulence factors is still poorly understood. The current study was aimed to determine the prevalence of different virulence genes in Enterococcus faecalis and Enterococcus faecium. For this purpose, 79 clinical isolates of Malaysian enterococci were evaluated for the presence of virulence genes. pilB, fms8, efaAfm, and sgrA genes are prevalent in all clinical isolates. In conclusion, the pathogenicity of E. faecalis and E. faecium could be associated with different virulence factors and these genes are widely distributed among the enterococcal species.